(untitled) (Confluenţe Bibliologice, 2014)
The article is an attempt to familiarize users with the „Pavel Proca” personal collection. The donation comes from the collection of books belonging to the playwright and theatre critic Pavel Proca, who has worked at the "Vasile Alecsandri" National Theatre of Balti. The collection includes 467 copies of various ﬁelds of science: philosophy, real science and applied arts, literature, history. The collection, in large measure, it is in Romanian language, but also contains books in Russian, Spain, Latin languages. "The Pavel Proca” personal collection contributes to enriching the cultural heritage of the institution.